The Analysis of Walkability Based on the Concept of Transit Oriented Development (TOD) - Padon, Apinya; Iamtrakul, Pawinee (Journal of Architectural/Planning Research and Studies (JARS), 2022)
Pedestrian is a basic element for urban sustainability, however in Thailand, pedestrians are at a high risk of accidents while access to transit stations. This is due to the reason that road facilities in Thailand has not been designed to support vulnerable road users. The purpose of this research is to study the walkability of transit stations by applying the concept of transit-oriented development (TOD). This study focused on the sample of 4 transit stations, namely Chatuchak Park Station, Phahonyothin Station Cultural Center Station, and Siam Station. By analyzing the walkability from the 3Cs criteria based on Transit Oriented Development (TOD) concept, including connectivity, convenience, and comfort, in which of each factor, it consists of 4 sub-factors. The evaluating scores for each factor was input into the Overlay Analysis according to the criteria of walkability in urban areas (1-100 scores). The results showed that the cultural center station had the lowest walkability value at 50.68, indicating access to a moderate level of walking. It is demonstrated that this station still needs to be renovated to allow for walking traffic access to the area. For Phahonyothin Station, Chatuchak Park Station, and Siam Station, it showed high walkability values in the range of 66-100, which demonstrated good walking access. Finally, the quality of the pedestrian surface still revealed damaged spots that need to be developed and resolved in order to promote walkability in the area for sustainable urban development.